2006
DOI: 10.1207/s15324796abm3101_14
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and quality of life in older adults: Influence of health status and self-efficacy

Abstract: Our findings support a social cognitive model of physical activity's relationship with QOL. Subsequent tests of hypothesized relationships across time are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
258
4
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(307 citation statements)
references
References 17 publications
29
258
4
16
Order By: Relevance
“…It has been argued that these constructs are hierarchically related to PA with proximal HRQOL (often represented by indices of physical and mental health status) predicting distal QOL (i.e., satisfaction with life) (Elavsky et al 2005;Motl and McAuley 2010). Similar to other studies on the PA-QOL relationship (McAuley et al 2006(McAuley et al , 2008, in this study, we conceptualized global QOL as a general satisfaction with life.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has been argued that these constructs are hierarchically related to PA with proximal HRQOL (often represented by indices of physical and mental health status) predicting distal QOL (i.e., satisfaction with life) (Elavsky et al 2005;Motl and McAuley 2010). Similar to other studies on the PA-QOL relationship (McAuley et al 2006(McAuley et al , 2008, in this study, we conceptualized global QOL as a general satisfaction with life.…”
Section: Introductionmentioning
confidence: 91%
“…This core construct of social cognitive theory has been found to have a pervasive impact on all areas of human functioning (Bandura 1997), including the ways in which PA influences QOL in older adults. Other mediating cognitive factors include outcome expectations, perceived social support, or self-regulation (Bandura 1997;McAuley et al 2003McAuley et al , 2006McAuley et al , 2011. There have been numerous attempts to explain the nature of the relationship between PA and QOL in older adults by considering self-efficacy and other social-cognitive variables (McAuley et al 2008;Rejeski and Mihalko 2001;White et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zullig and White (40) little research has examined the association between life satisfaction, self-rated health (SRH), and physical activity concurrently. However, the research on the relationship between physical activity and life satisfaction indicate a positive relationship between these two variables (6,13,25,28,31). In order to investigate the relationship between physical activity and life satisfaction Labudzki and Tasiemski (24) found that more than 50% of the respondents were classified as being highly active and that the total sample was "rather satisfied" with life "as a whole".…”
Section: Physical Activity and Satisfaction With Lifementioning
confidence: 99%
“…The benefits of regular exercise are widely acknowledged. Older adults can achieve specific benefits as exercise may offset the rapid decline in muscle mass, aerobic capacity (Chrysohoou et al 2014) and cognitive function (Hogan 2005;Snowden et al 2011), as well as enhancing psychological wellbeing and quality of life (McAuley et al 2006;Penedo and Dahn 2005). Despite these benefits, many older adults remain sedentary and few achieve the recommended levels of physical activity needed to accrue these health benefits.…”
Section: Introductionmentioning
confidence: 99%